Say we have an array of rectangular apertures sitting in the
x
−
y
x
−
y
plane and light hits this aperture traveling in the positive z direction.
There are
N
N
apertures arranged vertically (in the
y
y
direction). Each aperture has a width in the
x
x
direction of
a
a
and a height in the
y
y
direction of
b
b
.
For convenience, the apertures are aligned with their centers at
x
=
0
x
=
0
.
The apertures are equally spaced by a distance
d
d
.

The
electric field at some point

P
P
away from the array is

E
=
∑
n
y
=
1
N
E
n
y
(
a
,
b
)
E
=
∑
n
y
=
1
N
E
n
y
(
a
,
b
)
where

E
n
y
(
a
,
b
)
E
n
y
(
a
,
b
)
is the field from the

n
y
n
y
slit at that point. The

y
y
position of the center of the aperture is

(
n
y
−
1
)
d
(
n
y
−
1
)
d
so we write

y
=
(
n
y
−
1
)
d
+
y
′
y
=
(
n
y
−
1
)
d
+
y
′
and

(
x
,
y
′
)
(
x
,
y
′
)
is the position of a point in the aperture with respect to the center of the
aperture. We can write

E
n
y
(
a
,
b
)
=
∫
−
b
/
2
b
/
2
ⅆ
y
′
∫
−
a
/
2
a
/
2
ⅆ
x
ɛ
A
R
e
−
i
(
k
r
n
y
−
ω
t
)
E
n
y
(
a
,
b
)
=
∫
−
b
/
2
b
/
2
ⅆ
y
′
∫
−
a
/
2
a
/
2
ⅆ
x
ɛ
A
R
e
−
i
(
k
r
n
y
−
ω
t
)
If the point of observation is

(
x
P
,
y
P
,
z
P
)
(
x
P
,
y
P
,
z
P
)
then

r
n
y
=
[
(
x
P
−
x
)
2
+
(
y
P
−
y
)
2
+
(
z
P
−
z
)
2
]
1
/
2
r
n
y
=
[
(
x
P
−
x
)
2
+
(
y
P
−
y
)
2
+
(
z
P
−
z
)
2
]
1
/
2
but we take z to be zero at the aperture so

r
n
y
=
[
(
x
P
−
x
)
2
+
(
y
P
−
y
)
2
+
z
P
2
]
1
/
2
=
[
x
P
2
−
2
x
x
P
+
x
2
+
y
P
2
−
2
y
y
P
+
y
2
+
z
P
2
]
1
/
2
=
R
[
1
−
2
x
x
P
/
R
2
−
2
y
y
P
/
R
2
+
(
x
2
+
y
2
)
/
R
2
]
1
/
2
r
n
y
=
[
(
x
P
−
x
)
2
+
(
y
P
−
y
)
2
+
z
P
2
]
1
/
2
=
[
x
P
2
−
2
x
x
P
+
x
2
+
y
P
2
−
2
y
y
P
+
y
2
+
z
P
2
]
1
/
2
=
R
[
1
−
2
x
x
P
/
R
2
−
2
y
y
P
/
R
2
+
(
x
2
+
y
2
)
/
R
2
]
1
/
2
where

R
2
=
x
P
2
+
y
P
2
+
z
P
2
R
2
=
x
P
2
+
y
P
2
+
z
P
2
,
the distance from the origin. In the far field approximation

(
x
2
+
y
2
)
/
R
2
=
0
(
x
2
+
y
2
)
/
R
2
=
0
and we can write:

r
n
y
≈
R
[
1
−
2
x
x
P
/
R
2
−
2
y
y
P
/
R
2
]
1
/
2
.
r
n
y
≈
R
[
1
−
2
x
x
P
/
R
2
−
2
y
y
P
/
R
2
]
1
/
2
.
We use the first two terms in the binomial expansion and get

r
n
y
≈
R
[
1
−
x
x
P
/
R
2
−
y
y
P
/
R
2
]
=
R
−
x
x
P
/
R
−
y
y
P
/
R
=
R
−
x
x
P
/
R
−
[
(
n
y
−
1
)
d
+
y
′
]
y
P
/
R
=
R
−
x
x
P
/
R
−
(
n
y
−
1
)
ⅆ
y
P
/
R
−
y
′
y
P
/
R
r
n
y
≈
R
[
1
−
x
x
P
/
R
2
−
y
y
P
/
R
2
]
=
R
−
x
x
P
/
R
−
y
y
P
/
R
=
R
−
x
x
P
/
R
−
[
(
n
y
−
1
)
d
+
y
′
]
y
P
/
R
=
R
−
x
x
P
/
R
−
(
n
y
−
1
)
ⅆ
y
P
/
R
−
y
′
y
P
/
R
so now we have

E
n
y
(
a
,
b
)
=
∫
−
b
/
2
b
/
2
ⅆ
y
′
∫
−
a
/
2
a
/
2
ⅆ
x
ɛ
A
R
e
−
i
(
k
(
R
−
x
x
P
/
R
−
(
n
y
−
1
)
ⅆ
y
P
/
R
−
y
′
y
P
/
R
)
−
ω
t
)
.
E
n
y
(
a
,
b
)
=
∫
−
b
/
2
b
/
2
ⅆ
y
′
∫
−
a
/
2
a
/
2
ⅆ
x
ɛ
A
R
e
−
i
(
k
(
R
−
x
x
P
/
R
−
(
n
y
−
1
)
ⅆ
y
P
/
R
−
y
′
y
P
/
R
)
−
ω
t
)
.
We rearrange to get

E
n
y
(
a
,
b
)
=
ɛ
A
R
e
−
i
(
k
R
−
ω
t
)
e
i
k
(
n
y
−
1
)
ⅆ
y
P
/
R
∫
−
b
/
2
b
/
2
ⅆ
y
′
e
i
k
y
′
y
P
/
R
∫
−
a
/
2
a
/
2
ⅆ
x
e
i
k
x
x
P
/
R
.
E
n
y
(
a
,
b
)
=
ɛ
A
R
e
−
i
(
k
R
−
ω
t
)
e
i
k
(
n
y
−
1
)
ⅆ
y
P
/
R
∫
−
b
/
2
b
/
2
ⅆ
y
′
e
i
k
y
′
y
P
/
R
∫
−
a
/
2
a
/
2
ⅆ
x
e
i
k
x
x
P
/
R
.
We define

k
x
P
/
R
=
k
x
k
x
P
/
R
=
k
x
and

k
y
P
/
R
=
k
y
k
y
P
/
R
=
k
y
so that

E
n
y
(
a
,
b
)
=
ɛ
A
R
e
−
i
(
k
R
−
ω
t
)
e
i
k
y
(
n
y
−
1
)
d
∫
−
b
/
2
b
/
2
ⅆ
y
′
e
i
k
y
y
′
∫
−
a
/
2
a
/
2
ⅆ
x
′
e
i
k
x
x
′
E
n
y
(
a
,
b
)
=
ɛ
A
R
e
−
i
(
k
R
−
ω
t
)
e
i
k
y
(
n
y
−
1
)
d
∫
−
b
/
2
b
/
2
ⅆ
y
′
e
i
k
y
y
′
∫
−
a
/
2
a
/
2
ⅆ
x
′
e
i
k
x
x
′
E
=
ɛ
A
R
e
−
i
(
k
R
−
ω
t
)
∑
n
y
=
1
N
e
i
k
y
(
n
y
−
1
)
d
∫
−
b
/
2
b
/
2
ⅆ
y
′
e
i
k
y
y
′
∫
−
a
/
2
a
/
2
ⅆ
x
e
i
k
x
x
.
E
=
ɛ
A
R
e
−
i
(
k
R
−
ω
t
)
∑
n
y
=
1
N
e
i
k
y
(
n
y
−
1
)
d
∫
−
b
/
2
b
/
2
ⅆ
y
′
e
i
k
y
y
′
∫
−
a
/
2
a
/
2
ⅆ
x
e
i
k
x
x
.
We see that each piece of this is something we did before

E
=
ɛ
A
R
e
−
i
(
k
R
−
ω
t
)
e
i
k
y
(
N
−
1
)
d
/
2
sin
(
N
k
y
d
/
2
)
sin
(
k
y
d
/
2
)
b
s
i
n
c
(
k
y
b
/
2
)
a
s
i
n
c
(
k
x
a
/
2
)
E
=
ɛ
A
R
e
−
i
(
k
R
−
ω
t
)
e
i
k
y
(
N
−
1
)
d
/
2
sin
(
N
k
y
d
/
2
)
sin
(
k
y
d
/
2
)
b
s
i
n
c
(
k
y
b
/
2
)
a
s
i
n
c
(
k
x
a
/
2
)
or if we define

k
R
c
=
k
R
−
(
N
−
1
)
d
k
y
/
2
k
R
c
=
k
R
−
(
N
−
1
)
d
k
y
/
2
E
=
ɛ
A
a
b
R
e
−
i
(
k
R
c
−
ω
t
)
sin
(
N
k
y
d
/
2
)
sin
(
k
y
d
/
2
)
s
i
n
c
(
k
y
b
/
2
)
s
i
n
c
(
k
x
a
/
2
)
E
=
ɛ
A
a
b
R
e
−
i
(
k
R
c
−
ω
t
)
sin
(
N
k
y
d
/
2
)
sin
(
k
y
d
/
2
)
s
i
n
c
(
k
y
b
/
2
)
s
i
n
c
(
k
x
a
/
2
)

Comments:"This book covers second year Physics at Rice University."